Postural Risk Analysis Based on Rapid Upper Limb Assessment (RULA) Method for Manual Handling Workers in the Food Industry - M. Rofih; Siti Rahayu; Tri Ngudi Wiyatno (Yayasan Inovasi Kemajuan Intelektual, 2025)
Manual handling activities in the production process at PT XYZ pose a significant risk of musculoskeletal disorders due to non-ergonomic working postures. This study aims to assess postural risk levels among workers in the palletising section using the Nordic Body Map (NBM) and Rapid Upper Limb Assessment (RULA) methods. Based on responses from 15 workers, NBM results indicated an equal distribution of risk: five workers each were classified as low, moderate, and high risk. The most commonly reported areas of discomfort included the lower back, wrists, upper back, upper arms, elbows, and neck. RULA analysis yielded scores of 7 (very high risk) for lifting and placing boxes and 6 (high risk) for carrying boxes, indicating the need for immediate corrective action. These findings underscore the importance of ergonomic interventions, such as workstation redesign, ergonomic training, and assistive devices, to reduce the risk of chronic injury, improve worker well-being, and sustain productivity while minimising long-term healthcare costs.